Study On Carboxyl Functionalization Of Carbon Nanotubes Using Acid Treatment Method - Yunus, Muhammad Akmal Mohd (Universiti Sains Malaysia, 2017)
The introduction of carboxyl groups on carbon nanotubes (CNTs) surfaces by using acid treatment method are useful for further modification of CNTs. In this project, the effect of acid treatment time, concentration of acid (H2SO4/ HNO3) mixture and the acid ratio on functionalized CNTs is studied. Acid treatment was performed by impregnating CNTs in acid mixture of H2SO4 and HNO3 with different treatment time, different concentration of acid, and different ratio of acid. After functionalization of CNTs using acid treatment, Fourier Transform Infrared Absorption Spectroscopy (FTIR) and acid base titration using back titration characterization were carried out to determine the surface acid functional groups on CNTs qualitatively and quantitatively. Zeta Potential is using to study the charge and stability of functionalized CNTs. Other than that, the graphitization of the treated CNTs was examined using Raman Spectroscopy. In short, FTIR spectroscopy of CNTs treated by 10 M concentration of acid mixture of 16 hours with ratio 3:1 of H2SO4/HNO3 has the highest value of acid group concentration which is 4.15 mmol/g CNT. On the other hand, CNTs treated by 10 M concentration of acid mixture of 16 hours with ratio 3:1 of H2SO4/HNO3 shows the best result in zeta potential which is -38.6 mV. For Raman Spectroscopy, if G-band higher than the intensity of the D-band, it means that the CNTs have low defect and the surface of CNTs is still graphitized. If G-band lower than the intensity of the D-band, it indicates that the synthesized CNTs contained defects as well as low-graphitized forms of carbon.